The effect of class assignment on academic performance and the labour market: Evidence from a public federal university in Brazil - Henrique Z. Motte; Rodrigo Carvalho Oliveira (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Can students' rank in the ability distribution of their class impact their academic achievement? We aim to answer this question using a discontinuity generated by a rule for the distribution of students between classes at a prestigious Brazilian university. The rule means that in almost 30 per cent of its courses, the Federal University of Bahia allocates 50 per cent of the best students in the university entrance exam to the group that starts in the first semester, and the other 50 per cent to the group that starts in the second semester. We also explore the fact that the Federal University of Bahia was the first federal university in Brazil to adopt affirmative action for low-income individuals. In general, the results indicate that coming last among the best students of the first class negatively impacts student performance, and this effect is greater when considering students from affirmative action programmes and for courses in the field of technology. But the results in the labour market are not unique. Being in the first class could have positive or negative effects in terms of the labour market, depending on whether the students are part of the affirmative action quota or not.
Keywords: I0; J0; C4; 330; affirmative action; Brazil; education; labour markets; peer effects